Comparison between self‐assembling peptide nanofiber scaffold (SAPNS) and fibrin sealant in neurosurgical hemostasis. Issue 5 (16th June 2015) - Xu, Fei‐fan; Wang, Yue‐chun; Sun, Stella; Ho, Amy S.W.; Lee, Derek; Kiang, Karrie M.Y.; Zhang, Xiao‐qin; Lui, Wai‐man; Liu, Bai‐yun; Wu, Wu‐tian; Leung, Gilberto K.K.
Abstract: RADA16‐I is a synthetic type I self‐assembling peptide nanofiber scaffold (SAPNS) which may serve as a novel biocompatible hemostatic agent. Its application in neurosurgical hemostasis, however, has not been explored. Although RADA16‐I is nontoxic and nonimmunogenic, its intrinsic acidity may potentially provoke inflammation in the surgically injured brain. We conducted an animal study to compare RADA16‐I with fibrin sealant, a commonly used agent, with the hypothesis that the former would be a comparable alternative. Using a standardized surgical brain injury model, 30 Sprague–Dawley rats were randomized into three treatment groups: RADA16‐I, fibrin sealant or gelatin sponge (control). Animals were sacrificed on day 3 and 42. Astrocytic and microglial infiltrations within the cerebral parenchyma adjacent to the operative site were significantly lower in the RADA16‐I and fibrin sealant groups than control. RADA16‐I did not cause more cellular inflammatory response despite its acidity when compared with fibrin sealant. Immunohistochemical studies showed infiltration by astrocytes and microglia into the fibrin sealant and RADA16‐I grafts, suggesting their potential uses as tissue scaffolds. RADA16‐I is a promising candidate for further translational and clinical studies that focus on its applications as a safe and effective hemostat, proregenerative nanofiber scaffold as well as drug and cell carrier.